A Study on Patent Strategy and Management (International Journal of Innovative Research in Engineering & Management, 2021)
This study reorganizes and  conceptualizes existing patent strategy research, which has  origins in a variety of fields such as economics, law, and  management. As a result, it is expected that this analysis  will assist to organize and drive what is now a disjointed  and fragmented area of management research. The primary  framework presented focuses on two key topics in patent  strategy research: generic patent strategies and patent  strategic management. Furthermore, research in each of  these topics is usually mapped onto one or more of three  major domains—rights, licensing, or enforcement—within  which patent-related strategic activities are normally  carried out. The three patent strategy domains are  juxtaposed with various theoretical lenses used in patent  strategy research in two summary tables of previous  research. Finally, the paper discusses two potential areas  where research is starting to focus on their links to patent  strategy: companies' general appropriability strategies and  value creation strategies. An overall conceptual graphic  depicts the many study topics discussed in the article and  emphasizes the connections between them. By revealing  its numerous connections with the wider management field  and providing possibilities to address key unsolved  research issues, the reconceptualization and reframing of  previous research presented in this study promises to  improve scholarship on patent strategy. As a result, it  serves as a helpful road map for future management study  in this critical field.
Keywords: Appropriability; Isolating Mechanisms; Patent Strategy Value Capture